Discrimination and Access Barriers to the National Health Service Perceived by Trans People - Rodrigues, João (2020)
Introduction: Trans people, who need specific medical, surgical and psychological healthcare due to their condition, are confronted with discrimination, prejudice and stigma thus limiting their access to health services. The present study aims to assess barriers in trans health in three distinct public services (emergency, primary care and surgery). Material and Methods: A non‑controlled cross‑sectional study was conducted, using interviews with 71 trans people, after their sexology consult. An interview model was elaborated by the authors, adapting questions from the Trans Pulse Project and the 2015 US Transgender Survey. Results: Half of the trans people who used the services studied perceived discrimination by a healthcare provider. The use of prejudiced language was the most frequent perceived episode of discrimination and the emergency department was the place where it occurred with higher frequency. We found an association between episodes of perceived discrimination in family medicine and the discomfort felt in addressing trans health with the family physician. Discussion: The perceived discrimination felt by trans people was similar to the literature data, in emergency and family medicine services. The lack of knowledge of standards of care by health providers may reinforce barriers to trans healthcare, as seen in the literature. Conclusion: We found the need to study the impact of trans discrimination, around the country, as welll as evaluate and promote trans healthcare amongst healthcare providers.